Organization of telomeric and subtelomeric chromatin in the higher plant Nicotiana tabacum - Fajkus, J; Kovarík, A; Královics, R; Bezdĕk, M (Molecular & general genetics, 1995)
We have examined the structure and chromatin organization of telomeres in Nicotiana tabacum. In tobacco the blocks of simple telomeric repeats (TT-TAGGG)n are many times larger than in other plants, e.g., Arabidopsis thaliana or tomato. They are resolved as multiple fragments 60-160 kb in size (in most cases 90-130 kb) on pulsed-field gel electrophoresis (PFGE) of restriction endonuclease-digested DNA. The major subtelomeric repeat of the HRS60 family forms large homogeneous blocks of a basic 180 bp motif having comparable lengths. Micrococcal nuclease (MNase) cleaves tobacco telomeric chromatin into subunits with a short repeat length of 157 +/- 5 bp; the subtelomeric heterochromatin characterized by tandemly repeated sequences of the HRS60 family is cut by MNase with a 180 bp periodicity. The monomeric and dimeric particles of telomeric and subtelomeric chromatin differ in sensitivity to MNase treatment: the telomeric particles are readily digested, producing ladders with a periodicity of 7 bp, while the subtelomeric particles appear to be rather resistant to intranucleosomal cleavage. The results presented show apparent similarities in the organization of telomeric chromatin in higher plants and mammals.
Keywords: DNA rostlinná; Chromatin; Telomere; jedovaté rostliny; repetitivní sekvence nukleových kyselin; DNA, Plant; Repetitive Sequences, Nucleic Acid; tabák; Nicotiana; Plants, Toxic; telomery; chromatin